Discrete systems and digital signal processing with MATLAB - ElAli, Taan S., 1963- (CRC Press, 2016)
"Discrete linear systems and digital signal processing have been treated for years in separate publications. ElAli has skillfully combined these two subjects into a single and very useful volume. Useful for electrical and computer engineering students and working professionals a nice addition to the shelves of academic and public libraries. "Sum.